2016
DOI: 10.1002/dvdy.24464
|View full text |Cite
|
Sign up to set email alerts
|

Lung development requires an active ERK/MAPK pathway in the lung mesenchyme

Abstract: Background: Reciprocal epithelial-mesenchymal communications are critical throughout lung development, dictating branching morphogenesis and cell specification. Numerous signaling molecules are involved in these interactions, but the way epithelialmesenchymal crosstalk is coordinated remains unclear. The ERK/MAPK pathway transduces several important signals in lung formation. Epithelial inactivation of both Mek genes, encoding ERK/MAPK kinases, causes lung agenesis and death. Conversely, Mek mutation in mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Specimens were processed for paraffin (4 µm) or frozen (5-10 µm) sections. Experiments were performed as described (Boucherat et al, 2017). Slides were counterstained with Nuclear Fast Red, Alcian Blue or Hematoxylin.…”
Section: Histology Ihc and Immunofluorescence (If) Analysesmentioning
confidence: 99%
“…Specimens were processed for paraffin (4 µm) or frozen (5-10 µm) sections. Experiments were performed as described (Boucherat et al, 2017). Slides were counterstained with Nuclear Fast Red, Alcian Blue or Hematoxylin.…”
Section: Histology Ihc and Immunofluorescence (If) Analysesmentioning
confidence: 99%
“…Mek gene inactivation in the lung mesenchyme caused lung hypoplasia and tracheal defects because of increased apoptosis and reduced branching. Moreover, it indicated that ERK potentially interacts with the Wnt pathway during lung development [ 31 ]. The appearance of pulmonary dysplasia is characterized by reduced branching, increased apoptosis, and decreased mesenchymal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of both Mek genes in epithelial cells causes lung agenesis and may be fatal, and mutant Mek genes in mesenchymal cells present as lung hypoplasia, tracheal defects and neonatal death, but not kyphosis and omphalocele (31). Expression studies have indicated potential interactions of the ERK and Wnt signaling pathways during lung development (32). Dermo1 Cre -deletion rats are deficient in the mesenchyme-specific Mek gene function, which is associated with intrauterine growth restriction, giant omphalocele, kyphosis, lung hypoplasia, altered trachea patterning and still birth (33).…”
Section: Discussionmentioning
confidence: 99%